2001
DOI: 10.1159/000050029
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Genotype Distribution among Chronic Hepatitis B Virus Carriers in Shanghai, China

Abstract: Objective: Hepatitis B virus (HBV) genotype distribution is still unclear in China, where a high prevalence of HBV infection exists, although it is well known that HBV can be classified into six genotypes based on intergroup divergence. The aim of this study was to investigate the epidemiological distribution of HBV genotypes and to clarify further the genotype-related differences in the pathogenicity of HBV. Methods: Seminested PCR and restriction fragment length polymorphism analysis were conducted in 97 asy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
129
3
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(143 citation statements)
references
References 17 publications
(21 reference statements)
10
129
3
1
Order By: Relevance
“…Genotype C is the major genotype in this area (accounting for 83.2%), which is similar with HBV genotype distribution in China in previous reports [7,[14][15][16] . Genotype B was more frequently found in patients with mild hepatic inflammation (ASC), while genotype C in those with advanced liver diseases (CH and LC) (P < 0.05) ( result may correlate with the higher frequent mutations in the BCP of genotype C compared with to genotype B [8] .…”
Section: Discussionsupporting
confidence: 89%
“…Genotype C is the major genotype in this area (accounting for 83.2%), which is similar with HBV genotype distribution in China in previous reports [7,[14][15][16] . Genotype B was more frequently found in patients with mild hepatic inflammation (ASC), while genotype C in those with advanced liver diseases (CH and LC) (P < 0.05) ( result may correlate with the higher frequent mutations in the BCP of genotype C compared with to genotype B [8] .…”
Section: Discussionsupporting
confidence: 89%
“…These data thus suggested that certain genotype B strains might be associated with the development of HCC in young HBV carriers. Studies from Japan, Hong Kong, and China already confirmed the findings that HBV genotype C was associated with the development of HCC [49,50,54,55]. Recent data from the REVEAL-HBV study showed that the hazard ratio of cirrhosis after adjustment for age, gender, smoking, alcohol use, and HBV DNA level was 1.9 for genotype C compared to genotype B, suggesting genotype C was an independent risk factor for cirrhosis development in HBV carriers [56].…”
Section: Genotype and Subgenotypementioning
confidence: 84%
“…In contrast to the findings of the above studies in Vietnamese, a study by Song et al reported that genotype A was very commonly observed in HBV-infected Vietnamese patients (98.7%), that the pre-core mutation (G1896A) was not found, and dual core promoter mutations (A1762T/G1764A) were very rare in HCC patients (8%) and were not found in LC patients, CH patients or asymptomatic carriers (ASC) (33). The results reported by Song et al were very surprising, since the results of many other studies in East Asia and some in Vietnam, with only the exception of studies in the Philippines, showed that genotypes B and C were the major HBV genotypes in this region and mutations in the core promoter and pre-core regions were frequently found (8)(9)(10)(12)(13)(14)(15)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(34)(35)(36)(37)(38).…”
Section: Introductionmentioning
confidence: 95%